The Dynamics of Day and Night: Qur’anic Perspectives and Scientific Insights in Urban Contexts - Safei, Abdullah; Satiri, Iwan; Handoko, Agus (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
This study explores the dynamics of day and night through the integration of Qur’anic perspectives and scientific insights, with a particular focus on their implications in urban contexts. This research employs a descriptive qualitative method to examine in depth the harmony between science and religion, offering a holistic understanding of temporal rhythms that shape urban life. Data were collected from various secondary sources such as articles, books, and relevant journals. The findings indicate that recognizing both the physical and spiritual dimensions of day and night can contribute to enhancing social well-being, promoting sustainable urban living, and strengthening the balance between human productivity and community resilience.